The Correlation Between Health Belief Model and Consumption of Iron Tablets in Adolescence Girl - Aulia Rizky Ferina; Didien Ika Setyarini; Ita Yuliani (Universitas Pahlawan Tuanku Tambusai, 2025)
Iron tablets are one of the government's initiatives to prevent anemia, given the high prevalence of anemia among women aged 15 to 34 (48.9%). Adolescent girls still consume very less, however this varies by area. Data from the Malang City Health Office in 2022 shows that SMAN 8 Malang has consumption coverage in the 50-80% range. Perception has an impact on the choice to consume. The health belief model provides insight into the perception (HBM). The purpose of this study is to examine the connection between teenage girls' use of iron supplements and their HBM. Correlational analytics was employed in the study technique using a cross-sectional methodology. A proportionate random sample approach yielded 136 pupils in the population, which consisted of 10th graders. This research employed chi-square test data analysis, compliance with TTD consumption, and HBM surveys as its tools.While there was no significant correlation between the consumption of iron tablets in adolescent girls and perceived severity (p=0.303) and perceived vulnerability (p=0.330), there was a significant correlation between perceived benefits (p=0.000), barriers (p=0.006), cues to action (p=0.036), and self-efficacy (p=0.000). According to the study's findings, teenage girls who take iron pills have an association with their perceptions of the advantages, obstacles, signals to take action, and self-efficacy.s